Mobile Ad Effectiveness: Hyper-Contextual Targeting with Crowdedness - Andrews, Michelle; Luo, Xueming; Fang, Zheng; Ghose, Anindya (Marketing Science, 2016)
This research examines the effects of hyper-contextual targeting with physical crowdedness on consumer responses to mobile ads. It relies on rich field data from one of the world’s largest telecom providers who can gauge physical crowdedness in real-time in terms of the number of active mobile users in subway trains. The telecom provider randomly sent targeted mobile ads to individual users, measured purchase rates, and surveyed purchasers and nonpurchasers. Based on a sample of 14,972 mobile phone users, the results suggest that, counterintuitively, commuters in crowded subway trains are about twice as likely to respond to a mobile offer by making a purchase vis-à-vis those in noncrowded trains. On average, the purchase rates measured 2.1% with fewer than two people per square meter, and increased to 4.3% with five people per square meter, after controlling for peak and off-peak times, weekdays and weekends, mobile use behaviors, and randomly sending mobile ads to users. The effects are robust to exploiting sudden variations in crowdedness induced by unanticipated train delays underground and street closures aboveground. Follow-up surveys provide insights into the causal mechanism driving this result. A plausible explanation is mobile immersion: As increased crowding invades one’s physical space, people adaptively turn inwards and become more susceptible to mobile ads. Because crowding is often associated with negative emotions such as anxiety and risk-avoidance, the findings reveal an intriguing, positive aspect of crowding: Mobile ads can be a welcome relief in a crowded subway environment. The findings have economic significance because people living in cities commute 48 minutes each way on average, and global mobile ad spending is projected to exceed $100 billion. Marketers may consider the crowdedness of a consumer’s environment as a new way to boost the effectiveness of hyper-contextual mobile advertising. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mksc.2015.0905 .